Dopaminergic modulation of positive expectations for goal-directed action: evidence from Parkinson’s disease - Wolpe, Noham; Nombela, Cristina; Rowe, James B. (Frontiers in Psychology, 2015)
Parkinson’s disease (PD) impairs the control of movement and cognition, including the planning of action and its consequences. This provides the opportunity to study the dopaminergic influences on the perception and awareness of action. Here we examined the perception of the outcome of a goal-directed action made by medicated patients with PD. A visuomotor task probed the integration of sensorimotor signals with the positive expectations of outcomes (Self priors), which in healthy adults bias perception towards success in proportion to trait optimism. We tested the hypotheses that (i) the priors on the perception of the consequences of one’s own actions differ between patients and age- and sex-matched controls, and (ii) that these priors are modulated by the levodopa dose equivalent in patients. There was no overall difference between patients and controls in the perceptual priors used. However, the precision of patient priors was inversely related to their levodopa dose equivalent. Patients with high levodopa dose equivalent showed more accurate priors, representing predictions that were closer to the true distribution of performance. Such accuracy has previously been demonstrated when observing the actions of others, suggesting abnormal awareness of action in these patients. These results confirm a link between dopamine and the positive expectation of the outcome of one’s own actions, and may have implications for the management of PD.